2015
DOI: 10.1128/mbio.01508-15
|View full text |Cite
|
Sign up to set email alerts
|

Erratum for Boudry et al., Function of the CRISPR-Cas System of the Human Pathogen Clostridium difficile

Abstract: , 2015. The following statement should be added to the Acknowledgments section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Table of all unique type I PAMs found for the different subtypes and representative genera that contain the repeat cluster for which each PAM was determined. For previously described PAMs, a reference ID has been added which correspond to the following: 1[60], 2[61], 3[62], 4[63], 5[45], 6[64], 7[65], 8[46], 9[14], 10 [66], 11[67], 12[49], 13[68], 14[69], and 15[70]…”
mentioning
confidence: 99%
“…Table of all unique type I PAMs found for the different subtypes and representative genera that contain the repeat cluster for which each PAM was determined. For previously described PAMs, a reference ID has been added which correspond to the following: 1[60], 2[61], 3[62], 4[63], 5[45], 6[64], 7[65], 8[46], 9[14], 10 [66], 11[67], 12[49], 13[68], 14[69], and 15[70]…”
mentioning
confidence: 99%
“…S3). For example, the C. difficile 630Δ erm strain used in this work carries two cas operons ( 26 ). The first cas operon, CD2982-CD2975 , referred to as “full” encodes a complete set of proteins required for both interference and adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…The finding that the full cas operon is apparently non-functional is an unexpected one since sequence analysis of the products of the full operon reveals no potentially inactivating mutations in any of the genes. In the prior study, RNA-seq analysis of C. difficile 630Δ erm showed that the steady-state levels of transcripts of both cas operons are comparable and low in relation to an overall average transcription level under standard laboratory growth conditions with rather uniform coverage detected by both RNA-seq and qRT-PCR ( 26 ). To estimate the relative amounts of protein products of both operons, lysates of C. difficile 630Δ erm were analyzed by liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations